STRATEGI PENTING DALAM MENCEGAH ANEMIA: PENYULUHAN KESEHATAN UNTUK KEHIDUPAN YANG LEBIH SEHAT PADA REMAJA PUTRI DI KELURAHAN KARANGWARU, KECAMATAN TEGALREJO, YOGYAKARTA - Jeffry Andhika Putra; Kusmaryati Dwi Rahayu; Widya Kartika; I Ketut Mangku (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Anemia is a micronutrient problem that occurs throughout the world, especially in developing countries, where it is estimated to occur in 30% of the world's population. As a result of a lack of hemoglobin levels, it causes symptoms of lethargy, fatigue and fatigue quickly when carrying out activities which will have an impact on decreased concentration and learning achievement, and in the long term will have an impact on the quality of human resources, where young women are the future generation of the nation who will later supports determining the next generation. The results of basic health research in 2013 showed that anemia in adolescent girls increased to 48.9% in 2018. The aim of this community service is to provide information to adolescent girls about anemia and the importance of consuming blood supplement tablets. The methods used in this community service are lectures, question and answer discussions. This community service was carried out on November 23 2020, starting at 10.00 WIB until 12.00 WIB, at RW 4 Hall with a total of 40 participants. The result of this community service was an increase in young women's knowledge about anemia and the benefits of consuming blood supplement tablets